Bacterial isolation and bioconversion of organic materials to industrial platform chemicals - Sharma, Hem Kanta (My University, 2018)
Careful selection/isolation of the suitable microbial consortium for enzymatic saccharification of organic matters is a critical step in biofuels production. We isolated strains EF2, OW1-1 and HK2 from intestine of Eisenia fetida, municipal organic waste and forest soil respectively. The strains EF2, OW1-1 and HK2 have higher potential to produce various extracellular enzymes including cellulase and xylose/glucose isomerase (GI). The qualitative screening of strains using plate assay techniques was performed in standard agar plates to obtaine a zone of clearance. The 16S rRNA gene sequences of strains EF2 and OW1-1were identified as gram (+ve) Bacillus sp. whereas HK2 was a gram (-ve) Serratia marcescens. The Carboxymethyl cellulase (CMCase) activities of EF2 and OW1-1 were 35.307 ± 0.08 IU/ml and 29.92 ± 0.01 IU/ml, respectively, when 2.5% (w/v) of lactose was used as a carbon source at their respective optimal pH and temperature. The co-culture of Bacillus sp. strains EF2 and OW1-1 in contrast to their monoculture, showed 15% and 35.71% increased in CMCase activity respectively. Similarly, the strain S. marcescens HK2 preferred the temperature of 35 to 40 °C and pH of 8 to 9 for efficient GI production. The GI activity was high when 1.5% xylose and 1:3 ratio of peptone and yeast extract were used in the culture medium. The SDS-PAGE and zymogram revealed that the molecular weight of CMCase and GI were 60 and 63 kDa in Bacillus sp. (both EF2 and OW1-1) and S. marcescens HK2 respectively. This study discovered a novel finding that the strain S. marcescens HK2 can utilize low cost agricultural residue for production of GI and improved activity was observed in whole cell immobilization which can further minimize the cost of down streaming processing. Thus, all three bacterial strains could be a promising candidate for biofuels industries.
Keywords: Lignocellulose degrading enzymes; Xylose/glucose isomerase (GI) enzyme; Lignocellulosic biomass; Biomass derived biofuels; Bioconversion